2022
DOI: 10.1038/s41598-022-24486-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary examinations of athletes returning to high-intensity sport activity following SARS-CoV-2 infection

Abstract: After SARS-CoV-2 infection, strict recommendations for return-to-sport were published. However, data are insufficient about the long-term effects on athletic performance. After suffering SARS-CoV-2 infection, and returning to maximal-intensity trainings, control examinations were performed with vita-maxima cardiopulmonary exercise testing (CPET). From various sports, 165 asymptomatic elite athletes (male: 122, age: 20y (IQR: 17-24y), training:16 h/w (IQR: 12–20 h/w), follow-up:93.5 days (IQR: 66.8–130.0 days) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…It is important to emphasize that most of the performed CPET tests were carried out during the competitive part of the season, when it is expected for players to be in peak-level condition. These results coincide with the results of most previous studies dealing with this topic, which showed that there is a decrease in VO 2 max values in athletes who have overcome SARS-CoV-2 infection [18,19,23]. Even though VO 2 max values were lower than expected for athletes in all three groups (Wuhan, Delta, and Omicron), there was an obvious increase in both aerobic capacity and aerobic economy as the pandemic progressed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is important to emphasize that most of the performed CPET tests were carried out during the competitive part of the season, when it is expected for players to be in peak-level condition. These results coincide with the results of most previous studies dealing with this topic, which showed that there is a decrease in VO 2 max values in athletes who have overcome SARS-CoV-2 infection [18,19,23]. Even though VO 2 max values were lower than expected for athletes in all three groups (Wuhan, Delta, and Omicron), there was an obvious increase in both aerobic capacity and aerobic economy as the pandemic progressed.…”
Section: Discussionsupporting
confidence: 90%
“…There is currently a lack of scientific research regarding the impact of a particular strain of coronavirus on the severity of infection, clinical symptoms, and the development of cardiorespiratory and other forms of diseases, both in the general population and in athletes. With regard to athletes, the latest studies indicate a decline in functional abilities after SARS-CoV-2 infection, with increased respiratory and metabolic demands [18][19][20]. Furthermore, different forms of inflammatory heart diseases (myocarditis and pericarditis), decreased lung capacity, and aerobic endurance have been reported as a result of SARS-CoV-2 infection [9,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Female athletes reported slightly worse mood change scores compared to male athletes. Several studies found similar data regarding the post-COVID mental health of female athletes 20 , 38 , 54 , 55 . Notably, half of the athletes questioned did not need psychological support.…”
Section: Discussionmentioning
confidence: 66%
“… 7 The VE peak and VE/VCO 2 slope did not significantly change after infection in our case series ( Table 2 ), which is in accordance with previous studies. 32 , 35 Therefore, in the athletic population, pulmonary/ventilation function might not be the primary limitation of low VO 2peak and exercise intolerance in the long term, 5 , 6 or these factors could be gradually recovered over time. 32 , 36 …”
Section: Discussionmentioning
confidence: 99%